Efficiency of Regulations Regarding Consumer Credits In Macro-Prudential Framework: Case of Turkey - TUNAY, KAŞİF BATU (EGE UNIV, FAC ECONOMICS & ADMIN SCIENCES, 2017)
Before 2007-2008 global financial crisis, regulation system was based on the assumption that making each bank safe would make the banking system safe. After the crisis, it came out that macro prudential perspective was to be integrated and existing micro prudential regulation system should be supported. In this context, banking sector's procyclicality and by this behavior leading the way to increasing systemic risks has put swiftly countercyclical financial regulations on top of the agenda. This paper is aimed to test the effect of regulation changes made by Turkish banking authority (BDDK), put in effect in 2011 and 2013, in order to stabilize increase in consumer credits. Models established for this aim had estimated by using Ordinary Least Squers (OLS) and Generalized Method of Moments estimators. Evidences obtained from estimates have shown that countercyclical regulation changes has a significant restricting effect on consumer credits as admired by Turkish banking authority.
Keywords: Financial crisis; micro and macro prudential rules; systemic risk; procyclicality; countercyclical financial regulations